2017
DOI: 10.3390/f8090332
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Drought on Xylem Anatomy and Water-Use Efficiency of Two Co-Occurring Pine Species

Abstract: Exploring how drought influences growth, performance, and survival in different species is crucial to understanding the impacts of climate change on forest ecosystems. Here, we investigate the responses of two co-occurring pines (Pinus nigra and Pinus sylvestris) to interannual drought in east-central Spain by dendrochronological and wood anatomical features integrated with isotopic ratios of carbon (δ 13 C) and oxygen (δ 18 O) in tree rings. Our results showed that drought induces both species to allocate les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
37
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 72 publications
8
37
0
6
Order By: Relevance
“…Stable isotope analysis has become a major tool in the analysis of plant growth and vegetation change [1][2][3]. Tree rings allow retrospective views on growing conditions [4].…”
Section: Introductionmentioning
confidence: 99%
“…Stable isotope analysis has become a major tool in the analysis of plant growth and vegetation change [1][2][3]. Tree rings allow retrospective views on growing conditions [4].…”
Section: Introductionmentioning
confidence: 99%
“…Out the investigations we carried so far, it has been demonstrated that black pine is more resistant to drought [97]. The Scots pine is more sensitive to heat and drought [102], even after irrigation [103], due to the more drastic limitation of photosynthesis and transpiration, in the soil water deficit [104], by a stronger stomatal control [97]. Pines resistance to drought is due to their isohydric behavior [105], to the reduction of crown conductivity [106,107] and to a more efficient way to use the water [108] that leads to a diminished water loss.…”
Section: Scots Pine Vs Black Pine In Terms Of Radial Growth and Survmentioning
confidence: 99%
“…Out the investigations we carried so far, it has been demonstrated that black pine is more resistant to drought [97]. The Scots pine is more sensitive to heat and drought [102], even after irrigation [103], due to the more drastic limitation of photosynthesis and transpiration, in the soil water deficit [104], by a stronger stomatal control [97].…”
Section: Scots Pine Vs Black Pine In Terms Of Radial Growth and Survmentioning
confidence: 99%
See 2 more Smart Citations